VALIDITY OF PARENT-COMPLETED DEVELOPMENTAL SCREENING IN CHILDREN WITH NEW-ONSET EPILEPSY BELOW THE AGE OF 3. (18th May 2018) - Barton, Madelyn; Simard, Marie-Noëlle; Reiter-Campeau, Sandra; Lupien, Genevieve; Lamothe, Marie-Pierre; Chartrand, Dominic; Saint-Louis, Marie-Eve; Lortie, Anne; Major, Philippe; Diadori, Paola; Birca, Ala; Rossignol, Elsa; et al.
Abstract: BACKGROUND: Infants with childhood-onset epilepsies, including epileptic encephalopathies, are at high risk of developmental challenges such as motor and language delays. There has been a growing focus on developmental screening instruments due to the association between delayed development and long-term adverse outcomes, including negative impacts on health-related quality of life, school achievement and social participation. Therefore, children with developmental delays should be referred as early as possible to rehabilitation services such as occupational, physical, or speech therapy. Developmental screening using standardized tools is recommended in order to identify the high-risk children that require additional developmental assessments. The Ages and Stages Questionnaires (ASQ), a parent-completed developmental screening tool, is one of the more cited and recommended developmental screening tools. However, its utility in children with early-onset epilepsy has yet to be validated. OBJECTIVES: This study aimed to determine the validity of the ASQ for identifying children with new-onset epilepsy who require further professional developmental rehabilitation. DESIGN/METHODS: Fifty infants (25 males) with seizure onset under 3 years of age were prospectively recruited. Parents completed the ASQ-3 before the first clinic appointment. The ASQ-3 evaluates 5 domains of development. An ASQ score below 2 standard deviations (SD) on any one of the domains was considered abnormal. Once completed, all infants were evaluated by a multidisciplinary team including neurologists, occupational therapists, and physical therapists to determine if they should be referred for further rehabilitation interventions. Accuracy of the ASQ was calculated in terms of sensibility, specificity, positive predictive value (PPV) and negative predictive value (NPV). RESULTS: Mean age at the initial evaluation was 13.1 months (SD=8.22). Among the 50 infants, 36 (72%) received a score <-2 SD in at least one domain of the ASQ and 43 (86%) were referred for further rehabilitation services after the multidisciplinary assessment. The ASQ had a sensitivity of 81%, a specificity of 71%, a PPV of 93% and a NPV of 36% in identifying children with new-onset epilepsy who would require further rehabilitation services. CONCLUSION: The ASQ, a well-known parent-completed developmental screening tool, when abnormal shows adequate validity for the identification of children with early-onset epilepsy who require developmental assessments and interventions by rehabilitation professionals. Our results also provide further evidence that development delay is the rule rather than the exception in infants with new onset epilepsy.